Kesenian Prophetik Walisongo Dan Seni Wayang Purwa - Wawan Kardiyanto (Institut Seni Indonesia Surakarta, 2018)
Prophetic art is art that contains prophetic and divine values that synergize the universal values of humanity and divinity, namely truth, goodness, justice, and beauty. This research aims to describe the prophetic ethics in wayang. The analysis shows that Islam, as rahmatan lil alamin, certainly takes part in participating fastabiqul khairat to develop the progress of civilization through art. Wayang Purwa, with a set of gamelan along with stories and new puppet characters, have been created by Walisongo as a means for Islamic teachings which contain prophetic values. Keywords: Prophetic Art, Walisongo, Wayang Purwa.